Peran Guru Sebagai Figur Panutan Dalam Penerapan Keterampilan Saling Berbagi Di Era Disrupsi - Ratna Puspitasari; Septiani Resmalasari (Pendidikan IPS FKIP ULM, 2022)
Individual dualism has become a symptom of a society in the 21st century, with all its excesses, including materialism and selfishness, which are present at all levels of society. 21st-century teachers have a different role from conventional teachers, where they act as facilitators, collaborators, mediators, and motivators in learning and teaching activities with effective and fun learning targets that require abilities that are influenced by knowledge, training, and experience. The era of disruption makes a form of play that leads to selfishness, including through gadgets, so there are limitations in interacting directly with peers. Therefore, the teacher strives to encourage sharing skills as a form of skill to students so that they can receive and give to others who are instilled in the early to late class so that it affects the ongoing interaction. This study used Slavin Theory, about efforts to increase social contact among students to achieve goals and the role of teachers in learning and teaching activities. This study used qualitative methods with a phenomenological approach.Keywords: Teacher’s role, sharing, era of disruption